Vibration response of glass fiber composite multi-layer graded corrugated sandwich panels. (February 2022) - Yang, Jin-Shui; Yang, Fang; Han, Liu; Yang, Li-Hong; Wu, Lin-Zhi
Based on the criteria of equal total height and relative density, a series of glass fiber composite multi-layer graded corrugated sandwich panels (MLGCSPs) with different configurations is designed and fabricated by an in-house hot-molding secondary molding method. The effects of arrangement modes, graded corrugated cores and corrugated topologies on the vibration behavior of the present MLGCSPs are comprehensively investigated by the vibration shaker tests. The results reveal that the arrangement modes, graded arrangement and topologies of the corrugated cores all have significant influences on the frequency responses, and vibration reduction of the present MLGCSPs. The arrangement mode II and III generally have significantly higher resonant frequencies and vibration attenuation performance in the low frequency range, but the arrangement mode I shows better vibration reduction and isolation performance in the higher frequency range. It is possible to simultaneously achieve higher fundamental frequency and lower amplitude of the structures by optimizing the arrangement mode and gradient configuration. Subsequently, finite element simulation is carried out to systematically analyze the vibration responses of the composite MLGCSPs with different configurations. The consistency between numerical and experimental results is quite well. Finally, the effects of structural parameters on the vibration characteristics of the present structures are also revealed. Some conclusions are obtained, which can provide some meaningful guidelines for the vibration reduction design of such type of multi-layer structures.